Graphite-loaded cotton wool: A green route to highly-porous and solid graphite pellets for thermoelectric devices. (August 2020) - Mulla, Rafiq; Dunnill, Charles W.
Abstract: The high porosity of thermoelectric materials is a valuable feature to ideally reduce thermal conductivity without degrading electrical conductivity. This paper describes a unique low-temperature and direct method for making highly porous yet solid graphite pellets. Cotton wools were loaded with graphite particles, and pressed to yield low-density graphite pellets. The electrical and thermal properties of the resulting pellets have been studied. A significant reduction in the heat flow through the pellets has been observed as compared to a pure graphite pellet. For the porous pellets, the electrical conductivity was slightly lower than that of pure graphite pellets due to the charge scattering processes of the highly porous network, yet the thermal conductivity was drastically reduced with enhancements in Seebeck coefficients hence, a significant improvement in the thermoelectric property. Overall, the power factor was found to increase from 0.303 μWm −1 K −2 for solid graphite pellet to 0.424 μWm −1 K −2 for porous graphite pellet, showing a simultaneously improved power factor and reduced thermal conductance. The approach can be extended for other good thermoelectric materials to achieve further enhancements in their properties and useful to reduce material cost. Graphical abstract: Image 1 Highlights: A green and direct method for making highly porous yet solid graphite pellets has been presented. Significant reduction in the thermal conductance in porous pellets has been observed. The work can re-stimulate the use of porous graphite for thermoelectric applications.